Temperate Nuts - Mir, Mohammad Maqbool; Rehman, Munib Ur.; Iqbal, Umar.; Mir, Shabir Ahmad (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book focuses on the production technology of temperate nuts. It explores cultivar and plant improvement, development and selection of rootstocks, plant-water relations and irrigation, canopy architecture, and postharvest packaging of nut fruits. It also deals with organic approaches, biotechnological interventions, diseases, and pest management. Contributing authors address nut fruits such as walnut, pecan nut, chestnut, and hazel nut on different recent aspects. The development achieved in the fruit sector is indicative of the fact that there is growing demand of fruit produce. Temperate nuts with health benefits and market acceptability have best sources of fat, fiber, protein, and mineral. They provide dietary fiber, potassium, and a variety of health-protective bioactive compounds. Apart from the health benefits, production of temperate nuts improves the economy of the country as these are very good source of income and employment. In addition, there is wide diversificationin the production pattern of nuts globally. Increased production technology such as hybrids, high-yielding selections/ varieties, improved propagation techniques, and increased use of fertilizers and manures have brought spectacular increase in the production of nut fruits. This book is of interest to teachers, scientists, researchers, and scholars. Also, the book serves as additional reading material for undergraduate and postgraduate students of agriculture and horticulture. Horticulture nurseries and orchard industries also find this to be a useful read.
Chapter 1. Global scenario of temperate nuts -- Chapter 2. Nutritional composition of temperate nuts -- Chapter 3. Development and selection of rootstocks -- Chapter 4. Cultivars and genetic improvement -- Chapter 5. Improved propagation techniques in temperate nuts -- Chapter 6. Pollination management -- Chapter 7. Mineral nutrition -- Chapter 8. Plant water relations and Irrigation -- Chapter 9. Canopy architecture -- Chapter 10. Biotechnological interventions for improvement of temperate nuts -- Chapter 11. Organic approaches in temperate nuts -- Chapter 12. Shelf life enhancement -- Chapter 13. Package and storage of temperate nuts -- Chapter 14. Physiological disorders -- Chapter 15. Diseases of temperate nuts -- Chapter 16. Integrated pest management of temperate nuts.
Keywords: Agriculture; Food science; Plant biotechnology; Agriculture; Food Science; Plant Biotechnology